Pro-inflammatory and pro-resolving mechanisms in the immunopathology of arteriovenous fistula maturation. (4th May 2019) - Satish, Mohan; Gunasekar, Palanikumar; Agrawal, Devendra K.
ABSTRACT: Introduction : With high rates of arteriovenous fistula (AVF) failure, there is a continued need to predict other factors and mechanisms associated with maturation deficits. Given the central association of inflammation with AVF failure, with neointimal hyperplasia (NIH) as one such mechanism, inflammation must be considered in two endogenous ways, either pro-inflammatory or pro-resolving, resulting in inward or outward vascular remodeling. Areas covered : This review summarizes and critically evaluates the preclinical and interventional data underlying AVF failure in attempts to elucidate the necessary balance between inflammation and its resolution. Expert opinion : Understanding the pro-inflammatory and pro-resolving mechanisms underlying inward and outward vascular remodeling and NIH prevention with AVF maturation is a necessary effort to develop key diagnostic and therapeutic interventions towards the ongoing issue of long-term AVF patency. The ability for clinical application has progressed but is limited to the identification of key targets and pathways with little understanding of how they are related synergistically or antagonistically. Likewise, the balance between acute inflammation and pro-resolution requires pertinent temporal considerations necessary for timely therapeutic application and predictive measurement.